Gambaran Pola Makan Dan Kelelahan Kerja Pada Buruh Angkat Di PT. Karya Mandiri Prima Kabupaten Langkat - Huzaila Nur, Evawany Yunita Aritonang (Journal of Health and Medical Science, 2022)
Workers of lifting labor are estimated to have the risk of experiencing immediate work fatigue. The lack of nutrients present in the body of workers can cause a decrease in the human body's resistance to work, thereby causing fatigue and increasing workload. Keywords: Bamboo, inventory, Potential, Spread. The method carried out in this study was to see a picture of diet, diet, nutritional status, and work fatigue using questionnaires, food frequency, food recall and direct interviews of as many as 50 people at gas lifting workers at PT. Karya Mandiri Prima, Gebang District, Langkat Regency. From this method, the results were obtained, the workers of the adoptive workers at PT. Karya Mandiri Prima is mostly in the tired category, which is 33 people (66%), the very tired category is 17 people (34%). Another factor is the poor diet of 46 people (92%), and the good ones are only 4 people (8%). The type of food consumed by workers also has an effect on nutritional intake, namely as many as 41 people (82%) in the non-diverse category while the adoptive workers in the diverse category are only 9 people (18%). Meeting the needs of good nutrition can have a positive influence on the degree of health, efficiency and endurance of the labor body. Workers who have malnutrition conditions will experience obstacles in carrying out activities due to a decrease and slowdown in movement.